Answer:
Solving [tex](4g^2-9) \div (2g-3)[/tex] we get 2g+3
Option B is correct.
Step-by-step explanation:
We need to solve [tex](4g^2-9) \div (2g-3)[/tex]
We know that [tex]a^2-b^2=(a-b)(a+b)[/tex]
So, [tex]4g^2-9[/tex] can be written as [tex](2g)^2-(3)^2[/tex]
So, using above formula we will get:
[tex]4g^2-9\\=(2g^2)-(3)^2 \\Using \ formula a^2-b^2 = (a-b)(a+b)\\=(2g-3)(2g+3)[/tex]
So, numerator will become
[tex]\frac{(2g-3)(2g+3)}{(2g-3)} \\Simplifying:\\=2g+3[/tex]
So, solving [tex](4g^2-9) \div (2g-3)[/tex] we get 2g+3
Option B is correct.